Flexible δ-MnO2 nanosheet-infixed porous carbon nanofibers for capacitive deionization. (1st March 2023) - Zhang, Boshuang; Li, Jingjing; Hu, Bin; Wang, Yiwen; Shang, Xiaohong; Nie, Pengfei; Yang, Jianmao; Liu, Jianyun
Abstract: Birnessite-type manganese dioxide (δ-MnO2 ) is a typical pseudocapacitive material with the merits of natural abundance, environmental friendliness and high specific capacitance. Herein, the ultrathin δ-MnO2 nanosheets were successfully infixed on the electrospun porous carbon nanofibers (PCNF) by self-limitation reaction. The KMnO4 concentration and the hierarchical pore structure greatly affected the growth of δ-MnO2 nanosheets on the PCNF. Under the optimal condition, the as-prepared flexible δ-MnO2 @PCNFs electrode delivered extremely high specific capacitance of 455.3 F g − 1 . As a cathode in capacitive deionization (CDI), δ-MnO2 @PCNF presented the salt adsorption capacity of 15.9 mg g − 1, with ultrafast adsorption speed (1.8 mg g − 1 min −1 ). The δ-MnO2 @PCNF materials has excellent recycling stability in CDI device due to the interconnected structure of δ-MnO2 nanosheets inserted in PCNF.